Debating Migration as a Public Problem: Diasporic Stances in Media Discourse - Mălina Ciocea; Alexandru I. Cârlan (Romanian Journal of Communications and Public Relations, 2023)
This explorative study focuses on the construction of migration as a public problem through media discourse. Adopting Rogers Brubaker’s suggestion to approach diaspora as “a idiom, stance and claim”, we start from the assumption that journalists, when discussing migration, adopt diasporic stances, expressing loyalties and moral commitments and articulating them in the debate through practical arguments. Focusing on the media debates generated, in August 2010, by a declaration of Traian Băsescu, president of Romania, on the effects of migration, we identify three types of media discourse: the policy approach discourse, the professional accomplishment discourse and the citizen-as-victim discourse. We systematically relate these types of discourses with the arguments invoked for or against migration, and their subjacent loyalties. We conclude that through such diasporic stances, journalist engage diaspora in an instrumental manner, instituting a onedimensional perspective on it, along the traditional view of the social-political victimization.